2014
DOI: 10.1098/rspb.2013.2312
|View full text |Cite|
|
Sign up to set email alerts
|

A dynamic global equilibrium in carnivoran diversification over 20 million years

Abstract: The ecological and evolutionary processes leading to present-day biological diversity can be inferred by reconstructing the phylogeny of living organisms, and then modelling potential processes that could have produced this genealogy. A more direct approach is to estimate past processes from the fossil record. The Carnivora (Mammalia) has both substantial extant species richness and a rich fossil record. We compiled species-level data for over 10 000 fossil occurrences of nearly 1400 carnivoran species. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(101 citation statements)
references
References 54 publications
3
93
1
Order By: Relevance
“…However, evidence suggests diversity equilibrium for North American mammals (26), and for carnivores at a global scale (32). Our results strongly indicate that competition among several clades of canids and other carnivores drove the changes in diversification rates and the replacement of entire clades.…”
Section: Resultsmentioning
confidence: 60%
“…However, evidence suggests diversity equilibrium for North American mammals (26), and for carnivores at a global scale (32). Our results strongly indicate that competition among several clades of canids and other carnivores drove the changes in diversification rates and the replacement of entire clades.…”
Section: Resultsmentioning
confidence: 60%
“…It is unclear whether this approach is feasible for capture-mark-recapture methods that simultaneously estimate speciation, extinction and sampling rates [97], given that it may be difficult or even impossible to extract the large amounts of data from the fossil record needed to estimate the parameters of these methods.…”
Section: Realistic Models Of Fossil Preservationmentioning
confidence: 99%
“…They showed that ghost clades are explained substantially better by using confidence intervals on the oldest members of a clade that incorporate non-constant preservation. Other possible indirect proxies include the number of stratigraphic units [97], or the number of gap-bound sedimentary packages [100,104].…”
Section: Realistic Models Of Fossil Preservationmentioning
confidence: 99%
“…We preferred this method over more traditional approaches (2008; 2000) as it is recommended for paleontological data, especially under heterogeneous and incomplete sampling (Liow and Finarelli, 2014). In fact, under the Pradel approach the absence of a species from a time bin is interpreted as either real absence or as failed-to recognize presence.…”
Section: The Computation Of Speciation and Extinction Rates Pradel Mmentioning
confidence: 99%
“…As response variables, we used alternatively the two rates (i.e., extinction and speciation) as estimated by Pradel's models (see above) and SR as explanatory variable. As extinction and speciation rates represent probabilities (Liow and Finarelli, 2014;Finarelli and Liow, 2016), we converted them into "number of successes" or "number of failures" and included into GLMMs with a binomial distribution of errors and logit link function. In both regression models, linear and quadratic terms between SR and the response variables were calculated.…”
Section: Effect Of Sr On Diversification Ratesmentioning
confidence: 99%